Pengaruh Pengimplementasian Konsep Corporate Social Responsibility Berlandaskan Tri Hita Karana Terhadap Kinerja Keuangan dan Kesejahteraan Masyarakat Desa Adat - Ketut Tanti Kustina; Luh Putu Mirah Arisanti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
This study aims to analyze the effect of implementing the CSR concept based on Tri Hita Karana on the financial performance of LPD, the effect of implementing the CSR concept based on Tri Hita Karana on community welfare, the influence of LPD financial performance on the welfare of indigenous village communities, indirect influence on implementing csr concept based on Tri Hita Karana on the welfare of indigenous village communities through LPD financial performance in Subdistrict South Denpasar. The number of LPD in South Denpasar is as many as 11 units of LPD but there is 1 LPD that is not healthy, so the number of samples is used as many as 10 LPD. Respondents in this study were then selected 5 people on each LPD, so that the total sample of respondents was as many as 50 LPD employees. The analytical techniques used in this study are path analysis and sobel analysis. The results of the analysis are: Implementation of CSR Concept based on THK has a positive and significant effect on the financial performance and welfare of local communities LPD in South Denpasar District; Financial performance has a positive and significant effect on the welfare of the local community of LPD in South Denpasar Subdistrict; Financial performance is able to mediate the implementation of CSR concept based on THK on community welfare.